Impelension of Supervision by the Government Internal Supervision Apparatus (Apip) on Village Financial Management in Bolaang Uki District - Djakia, Haryono Suyono; Nur, Rafika; Djafar, Marwan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the implementation of supervision carried out by the Government Internal Supervision Apparatus (APIP) on village financial management in Bolaang Uki District, as well as to find out the obstacles faced in its implementation. Village financial management is an important aspect of transparent and accountable village development, so it requires an effective supervision mechanism. The research method used is an empirical juridical approach with data collection through field studies and documentation. The results of the study show that supervision by APIP has not been fully optimal, characterized by inconsistencies in the reporting and use of village funds. The inhibiting factors include limited human resources, low understanding of village officials on financial regulations, and weak coordination between APIP and village governments. Therefore, it is necessary to strengthen the capacity of APIP, increase training for village officials, and synergy between institutions to encourage village financial management in accordance with the principles of good governance.